Evaluation of a commercial interferon-γ release assay for the detection of SARS-CoV-2 T-cell response after vaccination - Imane Saad Albichr; Samy Mzougui; Arnaud Devresse; Hélène Georgery; Eric Goffin; Nada Kanaan; Jean Cyr Yombi; Leila Belkhir; Julien De Greef; Anaïs Scohy; Hector Rodriguez-Villalobos; Benoît Kabamba-Mukadi (Heliyon, 2023)
Objective: Evidence regarding the role of cellular immunity in protecting against COVID-19 is emerging. To better assess immune status, simple and robust assays measuring specific T-cell responses associated with humoral responses are needed. We aimed to evaluate the Quan-T-Cell SARS-CoV-2 test for measuring cellular immune responses in vaccinated healthy and immunosuppressed subjects. Methods: T-cell responses were assessed in healthy vaccinated and unvaccinated and unexposed healthcare workers to determine the sensitivity and specificity of the EUROIMMUN SARS-CoV-2 Quan-T-Cell IGRA test performed on vaccinated kidney transplant recipients (KTRs). Results: The EUROIMMUN SARS-CoV-2 Quan-T-Cell IGRA test showed good sensitivity (87.2%) and specificity (92.3%) at the calculated 147 mIU/mL cutoff, with an 88.33% accuracy. In KTRs, specific cellular immunity was lower than the antibody response; however, those with a positive IGRA result produced as much IFN-γ as healthy individuals. Conclusions: The EUROIMMUN SARS-CoV-2 Quan-T-Cell IGRA test showed good sensitivity and specificity for the detection of specific T-cell responses against the SARS-CoV-2 spike protein. These results present an additional tool for better management of COVID-19, especially in vulnerable populations.